1986
DOI: 10.1002/bjs.1800730506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stapling and handsuture for left-sided large bowel anastomosis

Abstract: One hundred patients undergoing elective left-sided colonic or rectal resections were randomly allocated to have an anastomosis performed either with the EEA stapling gun or by hand suture using a single layer of interrupted sutures. In six patients the anastomosis could not be performed with the stapling gun. Clinical leakage occurred in two of the remaining 94 cases; both had hand-sutured anastomoses. Radiological leakage was demonstrated in 13 further cases (7 stapled, 6 sutured); there was no statistical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 6 publications
2
21
0
3
Order By: Relevance
“…In the 1980s and early 1990s, to confirm the feasibility of mechanical stapling for anastomosis, many studies have compared the outcomes of anastomosis by mechanical stapling and hand suturing. [1][2][3][4][5][6][7][8] In regard to distal gastrectomy, there have been some studies for Billroth 1 gastroduodenostomy, which is the most commonly used in Japan, and these studies have demonstrated almost equivalent outcomes between the two methods of anastomosis. 9,10 Recently, to decrease the leakage rate and prevent bile juice reflux, Roux-en-Y reconstruction has come to be widely used after distal gastrectomy in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s and early 1990s, to confirm the feasibility of mechanical stapling for anastomosis, many studies have compared the outcomes of anastomosis by mechanical stapling and hand suturing. [1][2][3][4][5][6][7][8] In regard to distal gastrectomy, there have been some studies for Billroth 1 gastroduodenostomy, which is the most commonly used in Japan, and these studies have demonstrated almost equivalent outcomes between the two methods of anastomosis. 9,10 Recently, to decrease the leakage rate and prevent bile juice reflux, Roux-en-Y reconstruction has come to be widely used after distal gastrectomy in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…These instruments permit procedures such as total gastrectomy and low anterior colorectal resection, lengthy operations previously associated with a high incidence of complications, to be done relatively safely. Mechanical staplers have shortened the operation time, facilitated the performance of gastrointestinal anastomoses at sites with a poor field of view, and lowered the likelihood of suture failure [1][2][3]. Several prospective, randomized controlled studies have compared hand suturing with mechanical stapling in patients undergoing total gastrectomy and low anterior colorectal resection [1,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Whether surgical staples or handsewn techniques are used has no influence on leakage of the anastomosis. 8,9 Once a leak occurs, it can result in a localized abscess or frank peritonitis. This then leads to significant morbidity in the form of reoperation, a permanent stoma, and even death from fecal peritonitis.…”
mentioning
confidence: 99%